Pelatihan Pengolahan Data Statistik Menggunakan Aplikasi Spss Untuk Mahasiswa Semester Akhir - Rahayu Soraya; Putry Agung; Ali Mashari (Jurnal Dehasen Untuk Negeri, 2024)
Final semester students have difficulty processing statistical data using the SPSS application to complete the preparation of the thesis. In processing data, the SPSS application is needed. This SPSS application makes it easier for students to process statistical data. Therefore, it is necessary to introduce technology-based learning media related to the SPSS application through training. This training was attended by PGSD, PGPAUD, and Penjaskesrek students who were preparing their thesis and were preparing to process research statistical data. The purpose of this training is to increase students' knowledge of completing statistical data processing in the thesis using the SPSS application. The implementation of this training activity is the identification of student needs, preparation of learning materials, selection of learning methods, practical approaches, discussion, and evaluation. After the training was completed, it was seen that the discussion process went well and students enthusiastically asked questions. Students also experienced an increase in understanding and knowledge in using the SPSS application.